2020
DOI: 10.1111/cyt.12885
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of rosette patterns in variants of papillary thyroid carcinoma

Abstract: Introduction: The detection of rosette-like clusters (RLC) of follicular cells in thyroid carcinoma has been reported mostly in the columnar cell variant of papillary thyroid carcinoma (PTC). Despite the fact that diagnosing variants of PTC is no longer encouraged by The Bethesda System for Reporting Thyroid Cytopathology, the identification of cytomorphological features such as RLC linked with these tumours might help reduce possible misinterpretation in thyroid fine needle aspiration (FNA) cytology. We accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our case also displayed large RLCs of columnar tumour cells, similar to the Ylagen et al and Sen et al studies 12,14 . In their study, Dell'Aquila et al concluded that the presence of an RLC architectural pattern is most likely to be associated with malignant thyroid lesions and is seen in aspiration cytology samples, not in histological samples 16 . The RLC pattern may be seen in the tall cell subtype, hobnail subtype, and CCVPTC 16,17 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our case also displayed large RLCs of columnar tumour cells, similar to the Ylagen et al and Sen et al studies 12,14 . In their study, Dell'Aquila et al concluded that the presence of an RLC architectural pattern is most likely to be associated with malignant thyroid lesions and is seen in aspiration cytology samples, not in histological samples 16 . The RLC pattern may be seen in the tall cell subtype, hobnail subtype, and CCVPTC 16,17 .…”
Section: Discussionsupporting
confidence: 86%
“…16 The RLC pattern may be seen in the tall cell subtype, hobnail subtype, and CCVPTC. 16,17 In situations of thyroid FNAC with an equivocal interpretation or little neoplastic component, the identification of the RLC architectural pattern paired with the typical nuclear and cellular features of conventional PTC may raise suspicion for aggressive PTC subtypes. A close cytological mimicker of CCVPTC is a tall cell subtype of papillary carcinoma (TCV-PC) composed of respiratory-like tall columnar cells with eccentric basally located nuclei, granular cytoplasm, and distinct cell borders resembling Hurthle cells, prominent intranuclear inclusions, and typical nuclear features of PTC; however, nuclear pseudostratification is absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation